Characterization and Pollution Profile of the Tanning Industry by Distance in Gandong River, Indonesia - Sevi Dwi Pratiwi sevi; Suprijandani Suprijandani; Rachmaniyah Rachmaniyah; Sonu Kumar (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
River water quality is influenced by several factors, one of then is caused by industrial waste discharged into river bodies. Effluent discharged into water bodies contains heavy metals, pungent odours, and makes the colour of water in water bodies cloudy. the purpose of the study examined the effect of tannery effluent distance on the water quality of the Gandong River in Magetan Regency. Benefits For the company As a consideration to maximize WWTP processing actions so as not to pollute the river environment. for the surrounding community to know also the consequences caused by pollution of tanning industry waste so that they are more careful in reprocessing the use of river water. This type of the reseach was observational with a cross sectional approach. A purposive sampling technique was used. The data analysis methode was a correlation test by comparing laboratory test results with Gandong River water quality standards according to PP. RI. No 82 of 2001. Parametric statistical tests using Product-Moment Correlation to determine the relationsbetweenp of distance from the tannery industry affects the water quality of the Gandong River in Magetan Regency. The results showed that the water quality of Gandong River did not meet the requirements of COD 118 mg/l and colour 61.85 TCU/PtCo, at a distance of 250 m which exceeded the quality standards of COD 133 mg/l and colour 54.90 TCU/PtCo, at a distance of 500 m which did not meet the requirements of COD 89 mg/l, at a distance of 750 m which did not meet the requirements of COD 89 mg/l. temperature and TSS parameters. The highest results at a distance of 0 m of 27˚C and 368 mg / l meet the quality standard requirements for odour obtained odorous results. From the results of the study, it can be concluded that the parameters of pH, TSS, Temperature, and Odour still meet the quality standards and the parameters of colour, COD do not meet the quality standards. Based on the Product Moment correlation analysis, the relationship between distance and river water quality shows different values for correlation results that have a relationship, namely the parameters of odour, colour, COD and results that do not have a correlation of temperature and TSS. So the farther the distance from the pollutant source, the better the river water quality.